2007
DOI: 10.1038/sj.gt.3302898
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cell-type-specific promoters within the brain using lentiviral vectors

Abstract: The development of cell-type-specific mini-promoters for genetic studies is complicated by a number of issues. Here, we describe a general method for the relatively rapid screening of specific promoter activity in cell culture, in acute brain slice preparations and in vivo. Specifically, we examine the activity of an B3 kb promoter region from the neuroactive peptide cholecystokinin (CCK) compared to the commonly used cytomegalovirus promoter. We find a high degree of cell-type selectivity in vivo using lentiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…To examine the role of cortex-specific BDNF in modulating fear, we used a newly developed cortex-specific BDNF knockout mouse model (33). Expression of Cre recombinase in these mice includes the PL and neocortex but spares the more ventral IL, along with all other paleocortical and subcortical regions, with no expression in hippocampus, thalamus, striatum, hypothalamus, or amygdala ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the role of cortex-specific BDNF in modulating fear, we used a newly developed cortex-specific BDNF knockout mouse model (33). Expression of Cre recombinase in these mice includes the PL and neocortex but spares the more ventral IL, along with all other paleocortical and subcortical regions, with no expression in hippocampus, thalamus, striatum, hypothalamus, or amygdala ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lentivirus experiments used homozygous BDNF-floxed mice (34) (Bdnf tm3Jae /J; Jackson Labs), which possess loxP sites both upstream and downstream of exon 5 of the BDNF gene. The cortex-specific Cre mouse line, previously described as "transgenic line C" (33), was created when the coding sequence for Cre recombinase was placed downstream of a 3-kb CCK promoter. The cortexspecific Cre line was crossed to floxed BDNF mice, floxed-stop[Jackson Labs, Gt (ROSA)26Sor] lacZ reporter mice (35), and floxed-stop EGFP-tdTomato mice (36).…”
Section: Methodsmentioning
confidence: 99%
“…AAV-mediated expression may be less stable because a much smaller percentage of the virus is integrated. These vectors can be rendered cell type-specific by the choice of promoter [29], viral receptors [30], or spatial targeting strategies [31]. The volume and concentration of virus determines the spread in the tissue and opsin expression region.…”
Section: Basics Of Optogenetic Stimulationmentioning
confidence: 99%
“…Additionally, numerous studies have indicated that some other promoters, including the ovary specific promoter (OSP1) and the high-affinity folate receptors promoter (HAFR) (Godwin et al, 1995;Goldsmith et al, 1999), the modified rat probasin (rPB) promoters (Furuhata et al, 2003), and the neuroactive peptide cholecystokinin (CCK) promoter (Chhatwal et al, 2007), are of potential value for tissue specific expression of the tv-a gene. 1.2 Both isoforms of TVA molecule are sufficient for acceptance of the RCAS vectors As mentioned earlier, two isoforms, a transmembrane and a GPI-linked one, have been identified.…”
Section: Choice Of Specific Promotersmentioning
confidence: 99%